Penggunaan Etnomatematika pada Batik Humbang dalam Pembelajaran Tranformasi Geometri - Elda Kertiasa Sihombing; Roberto Silaen; Lamsoan Ritonga; Mangoloi P. Siregar; Agusmanto Hutauruk (Journal on Education, 2024)
Education and Culture are things that cannot be separated. Mathematical concepts are sometimes embedded naturally in people's culture. Mathematics with cultural nuances (ethnomathematics) can have a big influence on mathematics learning. This research aims to examine the use of ethnomathematics in Humbang Batik motifs in Transformational Geometry material. Research data was obtained by literature study, observation, interviews and documentation. Interviews were conducted with two Humbang batik craftsmen. This research is included in the type of exploratory research, namely exploring the form of Humbang batik motifs which can be utilized in the transformation geometry learning process. The approach used in this research is an ethnographic approach which aims to obtain an in-depth description and analysis of culture based on field research. The ethnomathematics in Humbang batik are reflection, translation, rotation and dilation in transformation geometry, which is found in Humbang Batik motifs such as coffee motifs, Sisingamangaraja swords, Gorga Simeol Meol, Sanduduk flowers, and others.